2023
DOI: 10.3389/fmicb.2022.1083432
|View full text |Cite
|
Sign up to set email alerts
|

The role of short-chain fatty acids in inflammatory skin diseases

Abstract: Short-chain fatty acids (SCFAs) are metabolites of gut microbes that can modulate the host inflammatory response, and contribute to health and homeostasis. Since the introduction of the gut-skin axis concept, the link between SCFAs and inflammatory skin diseases has attracted considerable attention. In this review, we have summarized the literature on the role of SCFAs in skin inflammation, and the correlation between SCFAs and inflammatory skin diseases, especially atopic dermatitis, urticaria, and psoriasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 138 publications
(185 reference statements)
0
17
0
Order By: Relevance
“…Through an immunofluorescence staining assay, we confirmed that BADGE treatment effectively decreased PPARγ expression ( Fig 3C ) and the mRNA levels of Cebpb and Pparg in the infected area (Figs 3D and S2A ). Considering that skin bacteria can modulate PPARγ signaling [ 22 , 23 ], we determined the amounts of skin bacteria in DMSO (control) and BADGE-treated mice [ 24 ]. We found that there was no significant difference in the expression of 16S rRNA between the two groups ( S2B Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Through an immunofluorescence staining assay, we confirmed that BADGE treatment effectively decreased PPARγ expression ( Fig 3C ) and the mRNA levels of Cebpb and Pparg in the infected area (Figs 3D and S2A ). Considering that skin bacteria can modulate PPARγ signaling [ 22 , 23 ], we determined the amounts of skin bacteria in DMSO (control) and BADGE-treated mice [ 24 ]. We found that there was no significant difference in the expression of 16S rRNA between the two groups ( S2B Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Our study’s community composition results ( Figure 5A ) reveal a significant reduction in the Firmicutes phylum within the gut of AR mice, coupled with an increase in the Bacteroidetes phylum. Members of the Bacteroidetes phylum are primary sources of acetic acid and propionic acid, whereas the Firmicutes phylum is recognized as the primary producer of butyric acid, a specific type of SCFA predominantly responsible for inhibiting the expression of HDACs ( Xiao et al, 2022 ). These findings suggest that gut microbiota dysbiosis in AR mice may potentially disrupt SCFAs metabolism, favoring HDAC overexpression and thereby likely contributing to the initiation of inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SCFAs benefit the intestinal barrier ( 47 ). Topical and oral administration of SCFAs or their derivatives have also been found to be effective in treating inflammatory dermatoses ( 48 ). Lactobacillus and Bifidobacterium may inhibit immune inflammation by increasing tryptophan (Trp) and Trp metabolites, maintaining intestinal barrier function on the one hand and reducing acne inflammation on the other ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%